Cascade Controller Design for a Single‐Stage Charger to Inspect Distortion Power Factor, and Grid‐Side Voltage Harmonics - Mahdi Maleki; Milad Rahimipour Behbahani; Alireza Jalilian (Engineering Reports)
ABSTRACT Electric vehicles (EVs) are poised to take center stage in daily transportation, gradually replacing vehicles solely reliant on combustion engines. Therefore, it is essential to address power quality issues associated with their integration into smart cities. Interleaved DC‐to‐DC boost converters are utilized to fulfill the objectives of voltage regulation and power factor correction (PFC) by controlling the duty cycle of their operational switches. The voltage regulation and reactive power compensation are addressed by the outer and inner control loops, respectively. Average current mode control is implemented to align the drawn current with the source voltage, even though it includes indispensable nonfundamental harmonic components. Voltage and current harmonics analyses are performed, and then the distortion power factor (DPF) is calculated. The charger's DPF and its efficiency factor are calculated to be 0.8583 and 0.935, respectively. To demonstrate the ascendancy of the control strategy, the charger's characteristics are compared to those of an uncontrolled charger with a proposed boost converter. The total harmonic distortion (THD) for the controlled current and voltage is significantly less than that of the uncontrolled charger design.